Market Discipline - Lane, Timothy (IMF Working Papers; Working Paper ;, 1992)
Under what circumstances can market forces prevent unsustainable borrowing? Effective market discipline requires that capital markets be open, that; information on the borrower's existing liabilities be readily available, that no bailout be anticipated, and that the borrower respond to market signals. This paper explores the implications of these conditions, and reviews some relevant empirical evidence.